Implementation of Design Thinking UI/UX Construction RAB Application at PT PLN (Persero) UID S2JB Lahat - Panggabean, Wahdyta Putri; Megawaty (International Journal Software Engineering and Computer Science (IJSECS), 2024)
An efficient and accurate Cost Budget Plan (RAB) plays an important role in the construction industry because it is directly related to project cost management. PT PLN (Persero) UID S2JB UP3 Lahat still uses manual methods to manage RAB, which causes the process of searching for documents and information to be slow and inefficient. To overcome this challenge, a website-based Construction RAB application was designed using the Design Thinking approach, which aims to improve the user interface (UI) and user experience (UX) in the RAB management process. This design process involves five stages of Design Thinking, namely empathize, define, ideate, prototype, and test. Using Figma, a UI/UX design prototype was developed as a visual and functional representation of the new design. The results of this development show a significant increase in the efficiency and effectiveness of RAB management at PT PLN (Persero) UID S2JB UP3 Lahat, including reducing the time needed to search for and access information related to RAB. The implementation of this application is expected to help companies manage RAB more effectively, increase productivity, and minimize errors in recording and managing costs.